Ð£Ð»ÑŒÑ‚Ñ€Ð°ÑÑ‚Ñ€ÑƒÐºÑ‚ÑƒÑ€Ð° Ð°Ñ€Ñ‚ÐµÑ€Ð¸Ð¹ Ð¿Ð¾ÑÐ»Ðµ Ð´ÐµÐ²Ð¸Ñ‚Ð°Ð»Ð¸Ð·Ð°Ñ†Ð¸Ð¸ Ð½Ð¸Ð·ÐºÐ¸Ð¼Ð¸ Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð°Ð¼Ð¸ Ð¸ Ð¸Ð¾Ð½Ð¸Ð·Ð¸Ñ€ÑƒÑŽÑ‰Ð¸Ð¼ Ð¾Ð±Ð»ÑƒÑ‡ÐµÐ½Ð¸ÐµÐ¼ - Byzov, D. V.; Repin, N. V.; Marchenko, L. N.; Govorukha, T. P.; Mikhaylova, I. P.; Synchykova, O. P.; Sandomirsky, B. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2011)
The report represents the data of electron microscopic study of small-diameter arteries following cryotreatment and ionizing irradiation. Combination of freeze-thawing with following irradiation by electron beam was shown to result in a complete devitalization of arteries while maintaining the connective-tissue frame intact.